OPTIMIZATION OF LAW ENFORCEMENT AND SOVEREIGNTY IN NATIONAL WATERS TO MAINTAIN STABILITY IN INDONESIA'S MARITIME TERRITORY - Prakasa , Novan Brhamasta Anugrah (ANTIS PUBLISHER, 2024)
To outline efforts to optimize law enforcement and sovereignty in Indonesia's national seas in maintaining the stability of the maritime area. Effective law enforcement and maintenance of ocean sovereignty are key elements to prevent conflicts and secure marine resources. This article discusses challenges and strategies in improving maritime law enforcement and securing Indonesia's maritime sovereignty. By integrating legal, security, and diplomacy approaches, Indonesia can strengthen its position as a strong maritime country and maintain the stability of its maritime areas. In conclusion, collaboration between law enforcement agencies, the military, and other stakeholders is essential to achieve this goal